Object signature in radio frequency - Fernandes, Rui Miguel Félix (2015)
The RF signature can be consider as a fingerprint of an object when submitted to electromagnetic radiation. Based on this concept, the initial goal of this work was to elaborate a comparative analysis of the Radio Frequency signature of different materials. Through the design of a prototype based on an adapted Wi-Fi network was developed an innovative system capable of distinguishing materials with the analysis of their interference in the propagated channel. In order to refine this distinction was utilized a signal processing tool, the Wavelet Transform. This technique serve as support tool of the system for a better differentiation of the studied targets. The versatility of this concept was proved through the analysis of signatures of static targets like metal, wood and plastic, as well as moving targets, giving the example of a moving human. Due to the promising results obtained, the initial objective of the work was expanded being also presented in this document the concept of intruder detection through a Wi-Fi network by the analysis of the Wavelet coefficients.